2020
DOI: 10.5336/dentalsci.2018-64331
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polishing Systems on the Staining Susceptibility of Composite Resins

Abstract: nde poster olarak sunulmuştur.ÖZET Amaç: Farklı polisaj sistemleri uygulanan iki kompozit rezin materyalinin renkleşmeye duyarlılığının karşılaştırılmasıdır. Gereç ve Yöntemler: İki farklı kompozit rezin (Clearfil Majestry Esthetic, Clearfil Majestry Posterior) kullanılarak, kalınlığı 2 mm ve çapı 8 mm disk şeklinde her bir materyalden 40 tane örnek hazırlandı. Her bir restoratif rezin grubu rastgele 4 alt gruba ayrıldı ve kontrol grubu dışında diğer üç grup farklı sistemlerle (Sof-lex, One-gloss, Enhance) cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…According to the studies conducted, an δEab value greater than 2.7 at 50%:50% confidence interval has been stated as clinically unacceptable. 14,15 The composite resin tested in our study showed a clinically acceptable color change when kept in different whitening mouthrinses. We think that the reason for this is that the composite resin we use does not contain Bis-GMA.…”
Section: Discussionmentioning
confidence: 67%
“…According to the studies conducted, an δEab value greater than 2.7 at 50%:50% confidence interval has been stated as clinically unacceptable. 14,15 The composite resin tested in our study showed a clinically acceptable color change when kept in different whitening mouthrinses. We think that the reason for this is that the composite resin we use does not contain Bis-GMA.…”
Section: Discussionmentioning
confidence: 67%